Identify coal distribution based on resistivity values using the Wenner configuration geoelectric method in Petai Village, Singingi Hilir District, Kuantan Singingi Regency - Hijrah Septia Anisa; Usman Malik; Krisman Sabar; Sherly Mutiara (Universitas Riau, 2024)
Research has been conducted on the distribution of coal using the Wenner configuration electric resistivity method. This research was conducted in Petai Village, Singingi Hilir District, Kuantan Singingi Regency, Riau Province. Data were collected using a resistivity meter. The data obtained are current data and potential differences. Data processing using Res2Dinv software whose result is in the form of resistivity of subsurface 2D images. The resistivity value of rocks on track 1 ranges from 28 – 23,584 Ωm with a depth of up to 12.4 meters. The resulting layers on track one include sand, sandstone, and conglomerate rocks. The resistivity values of the second trajectory range from 12.2 – 17,447 Ωm with a depth of up to 12.4 meters. The first layer has resistivity values ranging from 12.2 – 97.4 Ωm identifying the presence of sand. A second layer with resistivity values ranging from 97.4 – 275 Ωm identified the presence of anthracite-grade coal. A third layer with a resistivity value of 776 – 2,191 Ωm identified the presence of sandstone. A fourth layer with resistivity values 6,182 – 17,447 Ωm identified the presence of conglomerate rocks. The result of the interpretation of tracks one and two is that the distribution of coal is found on the second trajectory with a distribution pattern to the east. The distribution of coal spreads laterally on the trajectory of two research sites.